Fluxos e origens da migração: um estudo sobre trajetória e modos de vida de roboteiros em Luanda/Angola (2002-2021) - MIRANDA, Osmilde Augustos (2022)
The issue of migration, its flows and origins, has always attracted my attention, given that, during my life in Kazenga, my hometown, I witnessed the constant migration of families from the interior of the country. In this research, I intend to analyze migratory flows in Angola, adopting as an empirical reference the displacement of workers from rural communities and their ways of life as roboteiros, during the post-civil war period, 2002-2021, in Luanda, in the municipality of Cazenga. Investigating the ways of life of roboteiros allowed me to apprehend the trajectories of these subjects, regarding the forms of organization of their choices before and after migrating, as well as their cultural, political and social conceptions, through the reality they have built and rebuild as a group or class of a given society. However, I understand that the migratory flow of roboteiros to Luanda is related to survival strategies and maintenance of a specific way of accumulating material and symbolic goods that are lacking in their respective localities or regions of origin.